Worldwide risk assessment of phthalates and bisphenol A in humans: The need for updating guidelines - Dueñas-Moreno, Jaime; Mora, Abrahan; Kumar, Manish; Meng, Xiang-Zhou; Mahlknecht, Jürgen (Environment international, 2023)
Phthalates and bisphenol A (BPA) are compounds widely used as raw materials in the production of plastics, making them ubiquitous in our daily lives. This results in widespread human exposure and human health hazards. Although efforts have been conducted to evaluate the risk of these compounds in diverse regions around the world, data scattering may mask important trends that could be useful for updating current guidelines and regulations. This study offers a comprehensive global assessment of human exposure levels to these chemicals, considering dietary and nondietary ingestion, and evaluates the associated risk. Overall, the exposure daily intake (EDI) values of phthalates and BPA reported worldwide ranged from 1.11 × 10 to 3 700 µg kg bw d and from 3.00 × 10 to 6.56 µg kg bw d , respectively. Nevertheless, the dose-additive effect of phthalates has been shown to increase the EDI up to 5 100 µg kg bw d , representing a high risk in terms of noncarcinogenic (HQ) and carcinogenic (CR) effects. The worldwide HQ values of phthalates and BPA ranged from 2.25 × 10 to 3.66 and from 2.74 × 10 to 9.72 × 10 , respectively. Meanwhile, a significant number of studies exhibit high CR values for benzyl butyl phthalate (BBP) and di(2-ethylhexyl) phthalate (DEHP). Moreover, DEHP has shown the highest maximum mean CR values for humans in numerous studies, up to 179-fold higher than BBP. Despite mounting evidence of the harmful effects of these chemicals at low-dose exposure on animals and humans, most regulations have not been updated. Thus, this article emphasizes the need for updating guidelines and public policies considering compelling evidence for the adverse effects of low-dose exposure, and it cautions against the use of alternative plasticizers as substitutes for phthalates and BPA because of the significant gaps in their safety.